Marketing strategy in small and medium enterprises: A bibliometric analysis from 1989 to 2020 - Zurina Patrick; Ong Choon Hee (Human Resource Management Academic Research Society (HRMARS), 2022)
The marketing strategy is defined as an organization's integrated pattern of choices about products, markets, marketing activities, and marketing resources that add value to customers' interactions with the company and thus enable the company to achieve specific goals. Despite a growing interest in marketing strategy in SMEs, bibliometric and network analyses of marketing strategy in SMEs are uncommon in the vast literature. In order to close this gap, a bibliometric analysis of all publications in the Scopus database from 1989 to 2020 was conducted. Upon analyzing 202 articles, several parameters were determined, namely the trends in publications, prolific authors, productive journals, countries, academic institutions, research topics, and propose research opportunities for future research. The results suggest that C. Guräu from France is the most prolific author in this field, while the journal with the most publications in marketing strategy in SMEs is the Journal of Small Business and Enterprise Development. This present study also discovered that Indonesia led the number of publications in marketing strategy in SMEs with 30 total publications. Upon further systematic analysis using VOSviewer, 15 keywords were listed. Lagging far behind marketing strategy and SMEs, other relevant keywords are “Social Media” (frequency count: 11 times), “Business Performance” (8 times), and “Entrepreneurship” (7 times). These keywords give us an idea of the most research topics covered in the SMEs articles. Building on the outcomes retrieved from this analysis, researchers may better plan their studies and contribute better insights into their empirical investigations.